(untitled) (Research, Society and Development, 2023)
This research was entitled “Ethnogames: the impacts of a project developed after school hours at a riverside school in Manaus-Amazonas-Brazil” and had as general objective: to analyze what were the contributions of the Etnogames Project to the school community of the Municipal School São José I To obtain data, a methodology of bibliographical, descriptive, ethnographic and documental research was used, focusing on the type of qualitative and quantitative research. It was concluded that the actions of the Etnojogos Project allowed cultural appreciation and the construction of knowledge. In this way, using recreational activities, the project stimulated the search for intellectual knowledge and consequently the improvement in school performance through logical and linguistic development. Through Etnojogos, students interacted with each other to develop strategies in the making and painting of artifacts, researching the possibilities of how to play, how to improve their instruments, making them more accurate and efficient when playing. Thus, reaffirmed that, through playful activities, learning becomes more pleasurable.